NAVIGATING PUBLIC RELATIONS IN LOCAL GOVERNMENT CONFLICTS:: A Study on The Entertainment Venue Closure in East Java - Darmawati, Surya; Wulandari, Maulina Pia; Safitri, Reza (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
This study investigates the crucial function of the Public Relations (PR) Department of one of the Municipal administration offices in East Java in resolving issues between the administration and the public. The PR department is essential in overseeing the public perception by guaranteeing the clear and efficient distribution of information on government acts, policies, and initiatives.  The study is on the PR department's dual role as both an expert prescriber and a communication facilitato to improve government-public relations and mediate conflicts. The study employed a qualitative research methodology, which involved conducting interviews to investigate the role of the PR department. The findings suggest that the department is responsible for creating and executing communication strategies for the Mayor's office. They serve as a mediator between government officials and the public. The department also promotes the resolution of problems by working for the interests of both the government and the public, creating transparency and trust. Ultimately, the PR Department of the Municipal administration office is crucial for improving communication and maintaining constructive relations between the government and the public. The study suggests that enhancing strategic communication planning and implementing transparency measures would be beneficial in reinforcing public trust and promoting active participation.